Belief in group interdependence: Facilitating evacuee–host interactions after the Fukushima nuclear accident. Issue 5 (22nd February 2021) - Kobayashi, Tomoyuki; Yoshida, Kazuki; Takebayashi, Yoshitake; Goto, Aya; Kumagai, Atsushi; Murakami, Michio
Abstract: After the 2011 Fukushima nuclear accident, intercultural friction and aversion arose between evacuees and host community residents in relocation areas. We examined whether a belief in group interdependence —the extent to which an individual believes that group function is realized through interdependence with related other groups—is consistent with positive interactions between evacuees and hosts. A door‐to‐door survey of 77 evacuees and 75 hosts revealed that residents with an integrated social identity interacted favorably with both ingroup and outgroup members, and that a belief in group interdependence was consistent with the integration of social identity between the evacuee and host communities. Those findings suggest that a belief in group interdependence can reduce intercultural conflict by allowing both immigrants and host residents to acquire an integrated social identity without the dilemma of internalizing different cultures into an individual's mind.